1986
DOI: 10.1002/jcb.240300407
|View full text |Cite
|
Sign up to set email alerts
|

The coelomic envelope to vitelline envelope conversion in eggs of Xenopus laevis

Abstract: An amphibian egg recovered from the body cavity is enclosed by a coelomic egg envelope. Upon transport down the oviduct, the envelope is converted to the vitelline envelope. The coelomic and vitelline envelopes are distinct in terms of sperm penetrability, ultrastructural morphology, and radioiodination profiles. In this study, the macromolecular compositions of these two envelopes were determined. Isolated envelopes were compared by one- and two-dimensional gel electrophoresis, peptide mapping, and radiolabel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 20 publications
(17 reference statements)
0
33
0
Order By: Relevance
“…vealed that the anti-VE serum reacted with the major components of the CE. After absorption with egg extracts, the antiserum retained reactivity against most components of CE reported by Gerton and Hedrick (6) (Fig. 1).…”
Section: Incorporation Of L-t3h] Leucine By Cultured Oocytesmentioning
confidence: 51%
See 2 more Smart Citations
“…vealed that the anti-VE serum reacted with the major components of the CE. After absorption with egg extracts, the antiserum retained reactivity against most components of CE reported by Gerton and Hedrick (6) (Fig. 1).…”
Section: Incorporation Of L-t3h] Leucine By Cultured Oocytesmentioning
confidence: 51%
“…Besides these, our antiserum was also reactive to molecules with the M.W. smaller than 29K which have not been detected by ordinary Coomassie brilliant blue staining (6).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We asked if these alterations could contribute to the acquisition of sperm binding capacity during oocyte maturation. Because the proteolytic processing of gp43 in the oviduct is essential for unmasking the putative sperm binding sites in coelomic eggs (8,16,17,21), initially we determined if this processing can occur in immature oocytes. By analyzing the envelope proteins isolated from the immature stage 6 oocytes that have been forced to pass through the oviduct, we found that gp43 was cleaved to gp41 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This process involves ultrastructural changes in the envelope and processing of a major 43-kDa glycoprotein (gp43) in the CE to 41 kDa by a protease secreted from the oviduct (8,16,17). After several hours the coelomic egg passes through the oviduct and emerges as an oviposited egg.…”
Section: Introductionmentioning
confidence: 99%